Fast-food consumption among children according to Shari'ah perspective - Ramli, Mohd Anuar; Omar, Mohd Hazzman; Jamaludin, Mohammad Aizat (IIUM Press, International Islamic University Malaysia, 2021)
Fast-food consumption among children is becoming increasingly worrying as it is associated with unhealthy nutrition and its long-term health effects. This concern is due to signs of obesity among children and numerous other harmful diseases linked to low-nutrition, high-fat, and salt diets. According to Li et al. (2020), children aged 12 to 15 years in Malaysia consume fast food twice a week on average. Different factors influence fast-food intake. These include a rise in advertising, the growing number of fast-food restaurants, and shifting current lifestyles, particularly food selection. Accordingly, this study focuses on fast-food consumption from the Syari'ah point of view. This research adopts the library research, analysed selected documents, and summarised the Syari'ah rulings on fast-food consumption among children. The results show that Syari'ah ruling on fast-food consumption relies on habits of intake, fast-food sources and the side-effects on children, whether they are permissible (mubah), abominable (makruh) or prohibited (haram).